Dietary Patterns among Asian Indians Living in the United States Have Distinct Metabolomic Profiles That Are Associated with Cardiometabolic Risk - Bhupathiraju, Shilpa N; Guasch-Ferré, Marta; Gadgil, Meghana D; Newgard, Christopher B; Bain, James R; Muehlbauer, Michael J; Ilkayeva, Olga R; Scholtens, Denise M; Hu, Frank B; Kanaya, Alka M; Kandula, Namratha R (The Journal of nutrition, 2018)
Recent studies, primarily in non-Hispanic whites, suggest that dietary patterns have distinct metabolomic signatures that may influence disease risk. However, evidence in South Asians, a group with unique dietary patterns and a high prevalence of cardiometabolic risk, is lacking. We investigated the metabolomic profiles associated with 2 distinct dietary patterns among a sample of Asian Indians living in the United States. We also examined the cross-sectional associations between metabolomic profiles and cardiometabolic risk markers. We used cross-sectional data from 145 Asian Indians, aged 45-79 y, in the Metabolic Syndrome and Atherosclerosis in South Asians Living in America (MASALA) pilot study. Metabolomic profiles were measured from fasting serum samples. Usual diet was assessed by using a validated food-frequency questionnaire. We used principal components analysis to derive dietary and metabolomic patterns. We used adjusted general linear regression models to examine associations between dietary patterns, individual food groups, metabolite patterns, and cardiometabolic risk markers. We observed 2 major principal components or metabolite clusters, the first comprised primarily of medium- to long-chain acylcarnitines (metabolite pattern 1) and the second characterized by branched-chain amino acids, aromatic amino acids, and short-chain acylcarnitines (metabolite pattern 2). A "Western/nonvegetarian" pattern was significantly and positively associated with metabolite pattern 2 (all participants: β ± SE = 0.180 ± 0.090, P = 0.05; participants without type 2 diabetes: β ± SE = 0.323 ± 0.090, P = 0.0005). In all participants, higher scores on metabolite pattern 2 were adversely associated with measures of glycemia (fasting insulin: β ± SE = 2.91 ± 1.29, P = 0.03; 2-h insulin: β ± SE = 22.1 ± 10.3, P = 0.03; homeostasis model assessment of insulin resistance: β ± SE = 0.94 ± 0.42, P = 0.03), total adiponectin (β ± SE = -1.46 ± 0.47, P = 0.002), lipids (total cholesterol: β ± SE = 7.51 ± 3.45, P = 0.03; triglycerides: β ± SE = 14.4 ± 6.67, P = 0.03), and a radiographic measure of hepatic fat (liver-to-spleen attenuation ratio: β ± SE = -0.83 ± 0.42, P = 0.05). Our findings suggest that a "Western/nonvegetarian" dietary pattern is associated with a metabolomic profile that is related to an adverse cardiometabolic profile in Asian Indians. Public health efforts to reduce cardiometabolic disease burden in this high-risk group should focus on consuming a healthy plant-based diet.